Cover Feature: Plasma‐Enabled Ternary SnO2@Sn/Nitrogen‐Doped Graphene Aerogel Anode for Sodium‐Ion Batteries (ChemElectroChem 6/2020). Issue 6 (27th February 2020) - Ma, Yujie; Wang, Qianqian; Liu, Li; Yao, Shuyue; Wu, Wenjie; Wang, Zhongyue; Lv, Peng; Zheng, Jiajin; Yu, Kehan; Wei, Wei; Ostrikov, Kostya Ken
Abstract : The Cover Feature llustrates the formation of the SnO2 @Sn core–shell nanostructure on nitrogen‐doped graphene as an anode for sodium‐ion batteries, which is created through a plasma‐enabled fabrication process. The Na2 O/Sn interface can favor the performance of the batteries. More information can be found in the Article by Y. Ma et al. on page 1358 in Issue 6, 2020 (DOI: 10.1002/celc.201901999 ).